The link between early-life adversity and later alcohol use disorder: A role for microglia?Box 2: A Note on Microglia NomenclatureBox 3: Sex and region-specific differences in microgliaBox 4: Why is adolescence a critical timepoint regarding alcohol exposure? - Hannah D. Lichtenstein; Michelle K. Sequeira; Jessica L. Bolton (Neurobiology of Stress)
In the clinical literature, early-life adversity (ELA) has been highly associated with the later development of alcohol misuse and alcohol use disorder (AUD). Adolescence is a period of vulnerability for the development of neuropsychiatric disorders like depression and substance use disorders like AUD, both of which have been shown to have increased risk due to ELA. Experimentation with alcohol use in adolescence is quite common, but some adolescents that engage in alcohol experimentation become prone to alcohol misuse. Here, we review evidence that experiencing ELA prior to adolescent alcohol use could make individuals more susceptible to developing AUD, and consider the neural mechanisms that may underlie this vulnerability. We focus on the potential role of microglia, the resident immune cells of the brain, which are important for sculpting brain circuits during development and are highly sensitive to environmental perturbations. We discuss the microglia-mediated developmental processes within the stress- and reward-related regions of the brain, particularly those with corticotropin-releasing factor (CRF)-expressing neurons, and how these regions can be impacted by both ELA and alcohol use. Finally, we point to the gaps in the literature surrounding the link between ELA and AUD, and how investigating microglia in the context of this “2-hit model” may shed light on possible interventions and therapeutics that can be developed for this specific clinical population.